Realization of Multitone Continuous Wave Lidar - Rasul Torun; Mustafa M. Bayer; Imam U. Zaman; Jose E. Velazco; Ozdal Boyraz (IEEE Photonics Journal)
We have developed a multitone modulated continuous wave (MTCW) Lidar system made of a CW laser with multiple fixed RF tones for a high precision range finding and velocimetry. In this paper, the MTCW Lidar system has been studied analytically and numerically. A proof-of-concept experiment by employing 1550-nm light source and multiple radio-frequency (RF) tone modulations ranging from 50 MHz to 6 GHz has been performed to demonstrate proof of principle for range finding with <1-cm range resolution. We also provide sine fitting algorithms on the measured RF tones to extract the range information in a single shot RF measurement and demonstrate the ways to improve the resolution beyond the actual RF bandwidth.